Endogenous endothelin maintains coronary artery tone by endothelin type A receptor stimulation in patients undergoing coronary arteriography. Issue 2 (1st August 2000) - Kyriakides, Z S; Kremastinos, D T; Bofilis, E; Tousoulis, D; Antoniadis, A; Webb, D J
Abstract : OBJECTIVE: To examine the contribution of endothelin type A (ETA ) receptor stimulation by endogenously generated endothelin-1 (ET-1) to the maintenance of coronary vascular tone in humans. DESIGN: Controlled clinical study. SETTING: Tertiary cardiovascular referral centre. PATIENTS: 14 subjects were studied, seven with normal coronary arteries and seven with coronary artery disease, mean (SEM) age, 53 (2) years. INTERVENTIONS: After diagnostic coronary arteriography, BQ-123 (a selective ETA receptor antagonist; 100 nmol/min) in 0.9% saline, was infused into the left coronary artery at a rate of 1 ml/min for 60 minutes. Eight control subjects received saline alone. MAIN OUTCOME MEASURES: Blood flow velocity in the left anterior descending coronary artery, measured using a Doppler flow guidewire; coronary arteriography performed at baseline and immediately at the end of the BQ-123 or saline infusion to measure the diameter of proximal and distal left anterior descending coronary artery segments. RESULTS: The diameter of the proximal segment increased by 6 (2)%, while that of the distal segment increased by 12 (3)% after BQ-123 (both p < 0.05 v baseline). Coronary blood flow increased from 75 (10) to 92 (10) ml/min and coronary vascular resistance decreased from 1.99 (0.36) to 1.44 (0.22) mm Hg/ml/min after BQ-123 (both p < 0.05 v baseline). The response to BQ-123 of patients with and without coronary artery disease was similar. There was no effect of saline in the controls. CONCLUSIONS: Endogenously produced ET-1 contributes to the maintenance of basal coronary artery tone in humans by ETA receptor stimulation. The role of ETB receptors remains to be defined.